Why livestock matter - International Livestock Research Institute (International Livestock Research Institute, 2021)
Rising meat consumption is not a problem of the poor. In the global south, 690 million people are undernourished. Meat, milk and eggs are often the only sources of nutrients for families who live in poverty. whylivestockmatter.org